KERAJINAN KREATIF SEBAGAI MEDIA PERANCANGAN KAMPANYE SOSIAL PEMANFAATAN LIMBAH ESPRESSO DI PALEMBANG - Muhammad Hidayah; Iswandi, Heri; Halim, Bobby (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract: Epresso is a beverage produced from finely ground coffee beans, which are then pressed using a manual tool or an espresso machine filled with water to extract the liquid, resulting in what is known as espresso. Once the espresso is prepared, there is waste generated by coffee makers, leading to accumulated garbage. This is the reason why the author has created a social campaign design to promote the utilization of espresso waste in Palembang city.